2013
DOI: 10.1007/s00128-013-1113-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Copper Concentrations on Gills of White Shrimp (Litopenaeus vannamei, Boone 1931)

Abstract: The objective of this study was to measure the copper (Cu) concentration in gills of juveniles Litopenaeus vannamei after exposure to Cu at sublethal concentrations, and to evaluate its effect upon the structure of gill tissue. The Cu concentration in gills of control shrimp was 0.075 mg/kg. Copper concentrations increased significantly by 147 %, 180 % and 205 % in gills of shrimp exposed to 0.675, 1.325 and 2.010 mg Cu/L, respectively. After exposure to 0.675 mg Cu/L for 15 days, gill tissue hyperplasia was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Frías-Espericueta et al (2008b) determined the survival and possible histological alterations in the gills and hepatopancre-as of L. vannamei juveniles exposed to copper sulfate and found that the mortality of shrimp juveniles during 96 h of exposure was 50% (96-h LC 50 ) at a concentration of 35.12 mg L −1 , whereas the absence of pillar cells, loss of regular structure of the cuticular epithelium, and multifocal necrosis were observed after 3 weeks of exposure to a con-centration of 1.756 mg L −1 . Cu-related histological alterations were also reported by Soegianto et al (2013) and Qian et al (2020) in L. vannamei juveniles. Soegianto et al (2013) found that after 15 days of exposure to 0.675 mg L −1 , tissue hyper-plasia was evident in the filaments, which resulted in a narrowing of the hemolymphatic lacunae.…”
Section: Occurrence Of Metals In the Water And Assessment Of Metal Water Qualitymentioning
confidence: 59%
See 1 more Smart Citation
“…Frías-Espericueta et al (2008b) determined the survival and possible histological alterations in the gills and hepatopancre-as of L. vannamei juveniles exposed to copper sulfate and found that the mortality of shrimp juveniles during 96 h of exposure was 50% (96-h LC 50 ) at a concentration of 35.12 mg L −1 , whereas the absence of pillar cells, loss of regular structure of the cuticular epithelium, and multifocal necrosis were observed after 3 weeks of exposure to a con-centration of 1.756 mg L −1 . Cu-related histological alterations were also reported by Soegianto et al (2013) and Qian et al (2020) in L. vannamei juveniles. Soegianto et al (2013) found that after 15 days of exposure to 0.675 mg L −1 , tissue hyper-plasia was evident in the filaments, which resulted in a narrowing of the hemolymphatic lacunae.…”
Section: Occurrence Of Metals In the Water And Assessment Of Metal Water Qualitymentioning
confidence: 59%
“…Cu-related histological alterations were also reported by Soegianto et al (2013) and Qian et al (2020) in L. vannamei juveniles. Soegianto et al (2013) found that after 15 days of exposure to 0.675 mg L −1 , tissue hyper-plasia was evident in the filaments, which resulted in a narrowing of the hemolymphatic lacunae. Furthermore, ne-crosis and loss of hemolymphatic lacunae were observed in the gills of shrimp exposed to 1.325 mg L −1 and 2.010 mg L −1 .…”
Section: Occurrence Of Metals In the Water And Assessment Of Metal Water Qualitymentioning
confidence: 59%
“…Osmoregulatory capacity also was significantly reduced after 15 d exposure to 0.6 mg Cu/L, and at a concentration of approximately 0.7 mg Cu/L, for the same exposure period, Cu caused hyperplasia of gill tissue in postlarvae of L . vannamei ; necrosis of this tissue was observed from 1.3 mg Cu L −1 . In shrimp, metals tend to accumulate in the gill tissues, causing cytological and histochemical damage to the gill epithelium .…”
Section: Discussionmentioning
confidence: 91%
“…Regarding other ecotoxicological endpoints, many studies on metal toxicity using shrimp, including whiteleg shrimp L . vannamei , have been published . Responses such as survival, growth, feeding, gill functions, oxygen consumption, histopathological damage, and others have been shown to be suitable for measuring metal contamination .…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater fish uptake waterborne Cu mainly through the gills, followed by the skin and intestine [16]. From toxicological studies it has been demonstrated that elevated copper concentration in water can lead to increased copper levels in the gills [17,18], and it alters the function of the gills by causing severe ion regulation, gas exchange, and excretion of metabolic waste products [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%